RESEARCH METHODS OF ISLAMIC PREACHING SCIENCES IN THESIS & DISSERTATION WRITING WITH A QUALITATIVE RESEARCH APPROACH - Siti Nuri Nurhaidah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Written theses and dissertations must be unique scientific studies that are either completed or have not been previously investigated. The main criteria for theses and dissertations should be the determination of the title, grand theory, and research idea as well as originality, to ensure that the scientific work produced is not just testing a theory or previous research findings. However, it can contribute fresh ideas and novel research to the study of Islamic preaching. Writing theses and dissertations can also give students research expertise that they can use later on in their studies of Islamic preaching. Students will gain real new experiences through the process of discovery, study, and in-depth scientific thinking about the science of islamic preaching by studying and examining the most recent research areas. Islamic studies lecturers direct the orientation to expertise and classes in the schools overseen by this compartment in accordance with their preferences. It is preferable if Islamic studies lecturers initially have the flexibility to select their compartment. The function of developing expertise or a specific subject requires lecturers who have specialized in that area to maintain a commitment to that function or subject. Tesis dan Disertasi yang ditulis harus merupakan kajian original keilmuan yang ada atau belum pernah diteliti oleh peneliti sebelumnya. Penetuan judul, grand teori dan konsep penelitian serta orisinalitas tesis dan disertasi harus menjadi syarat utama, sehingga karya ilmiah yang dihasilkan tidak hanya sekedar menguji suatu teori atau temuan penelitian sebelumnya. Namun dapat memberikan teori dan kontribusi baru di bidang ilmu dakwah. Penulisan tesis dan disertasi juga dapat memberikan pengalaman meneliti bagi mahasiswa untuk melakukan penelitian berikutnya, ketika mereka telah terjun di medan dakwah. Dengan mengkaji dan mengeksplorasi bidang-bidang penelitian terkini, mahasiswa akan mendapatkan pengalaman baru secara nyata melalui proses penemuan, pengkajian, penelaahan dan pemikiran ilmiah yang mendalam tentang ilmu dakwah. Para dosen Islamic studies sesuai preferensinya memandu orientasi amaliyah Islam tersebut pada keahlian dan matakuliah-matakuliah di fakultas-fakultas yang bernaung di bawah kompartemen tersebut. Sebaiknya para dosen Islami studies memiliki kebebasan awal untuk memilih kompartemennya. Dosen telah masuk ke suatu bidang keahlian ilmu perlu ada komitmen berkelanjutan atas fungsi pengembangan keahlian atau matakuliah tertentu.